P 148 Associations of alpha and theta band power with default mode network BOLD signal in Alzheimer's disease – a simultaneous fMRI-EEG study. Issue 10 (October 2017) - Brueggen, K.; Berger, C.; Fiala, C.; Babiloni, C.; Teipel, S.
Abstract : Background: In healthy adults, simultaneous resting–state fMRI–EEG studies found positive associations of fMRI BOLD signal in regions of the default mode network (DMN) with posterior alpha band power, and negative associations with frontal theta band power. In Alzheimer"s disease (AD), simultaneous fMRI–EEG has not been studied yet. However, fMRI studies showed a decreased activity within the DMN, while EEG studies revealed decreased power within the alpha band at posterior electrodes and increased power within the theta band across widespread regions. Using simultaneous fMRI–EEG, we investigated the association of DMN BOLD signal with alpha and theta band power in AD patients compared to healthy controls (HC). We hypothesized to find reduced associations for alpha band power and increased associations for theta band power in the AD group. To assess whether the association strength varies with disease severity, we tested for an interaction with global cognition and episodic memory performance, expecting to find a significant interaction effect with decreased cognitive performance. Methods: Simultaneous resting–state fMRI–EEG was recorded in 14 patients with mild AD and 14 HC (matched for age, gender and education), using a 32-channel MR-compatible EEG system. We administered the MMSE and a verbal episodic memory task of theConsortium to Establish a Registry for Alzheimer's Disease(CERAD) battery. Power within the total alpha band (8–12 Hz) as well as alpha sub-bands (8–10 Hz, 10–12 Hz) was computed from pooled occipital electrodes; power within the theta band (4–7 Hz) was computed from pooled frontal electrodes. In voxel-wise linear regression analyses, we regressed the time series of the BOLD signal on the time series of the power within each EEG band and on the cognitive test scores. T -tests at the individual level and across groups were used to test for main and interaction effects of EEG power and cognitive test scores. Results: The AD group showed significantly decreased positive associations of BOLD signal and power in the total alpha band in clusters within the superior, middle and inferior frontal cortex, as well as the inferior temporal lobe and thalamus, compared to the HC group ( p  < 0.01, uncorr., cluster size ⩾50 voxels). This group effect was accompanied by a high inter-individual heterogeneity. Regarding power in the upper alpha sub-band, decreased associations were found in similar regions. For power in the lower alpha band, the AD group showed significantly decreased positive associations in scattered clusters within the superior frontal lobe, compared to the HC group. Results on the associations between DMN BOLD signal and theta power as well as on the interaction with cognitive performance will be presented at the conference. Discussion: The results of our study suggest that the positive association between EEG alpha power and BOLD signal is reduced in AD patients. This was most prominent in cortical DMN and thalamic regions, which might be due to altered functional interaction between DMN regions. Additionally, this group effect was more pronounced in the upper alpha sub-band, compared with the lower alpha sub-band. Our study adds to the understanding of the relationship between EEG and fMRI resting-state characteristics in AD. As EEG is more widely available and cost-effective than fMRI, this may yield important implications for future clinical use.